Tratamento cirúrgico de canino incluso em mento: relato de caso - Hyppolito, João Octávio Pompeu; Paies, Marina Bozzini [UNESP]; Veras Filho, Ruy de Oliveira [UNESP]; Florian, Fernanda [UNESP]; Vieira, Eduardo Hochuli [UNESP] (My University, 2011)
The mandibular and maxillary canines when well positioned in the arch, are important functionally and aesthetically. Although these teeth are frequently malpositioned in the dental arch, their absence of eruption are not common, occuring more frequently with the maxillary canine than the mandibular canine. The canine transmigration is a well-known pre eruptive phenomenon in which the tooth goes thru the facial midline, occurring more frequently in the mandible than in maxila. Females are more susceptible than males and the right side more than the left one. Normally the patients do not show any symptoms, and this condition is observed during radiographic exams to diagnose the late exfoliation of the deciduous canine or for any other purpose. Due to the relationship between impacted canines and pathologic lesions, infection, trauma to the adjacent teeth, pain, ectopic eruption and interference with prosthesis, it´s indicated the surgical extraction of these teeth. The goal of this article is to describe and discuss the surgical treatment of an impacted canine (43) in the chin.

Os caninos maxilares e mandibulares, quando estão em sua posição normal, são importantes dos pontos de vista estético e funcional. Estes são dentes frequentemente mal posicionados, porém a falha do irrompimento de canino mandibular é pouco comum, sendo mais frequente a inclusão de caninos maxilares. A transmigração – migração pré-eruptiva de um dente através da linha média – de caninos, por sua vez, é relatada na mandíbula com maior frequência do que na maxila. O gênero feminino é mais acometido que o masculino e o lado esquerdo é mais prevalente que o direito. Normalmente, os pacientes não apresentam sintomas; portanto, os dentes inclusos são descobertos em exames radiográficos para diagnosticar a demora da esfoliação do canino decíduo ou por qualquer outra finalidade. Devido a possíveis associações de caninos inclusos com lesões patológicas, infecção, lesão aos dentes vizinhos, dor, erupção ectópica e interferência com próteses, indica-se a remoção cirúrgica destes dentes. Este trabalho tem por objetivos descrever e discutir um caso clínico-cirúrgico de canino (43) incluso em mento.
Surgical treatment of an impacted canine in the menton: case report
Keywords: Canine; Unerupted; Mandible; Canino; Dentes Inclusos; Incluso; Mandíbula